2004
DOI: 10.1051/rnd:2004022
|View full text |Cite
|
Sign up to set email alerts
|

Crop-residue supplementation of pregnant does influences birth weight and weight gain of kids, daily milk yield but not the progesterone profile of Red Sokoto goats

Abstract: -The parameters investigated in this study with the objective of evaluating growth, lactation and reproductive performances, included birth weight, litter size, 0-90 days gain and average daily gain of kids as well as the milk yield and progesterone profile of Red Sokoto does supplemented with crop-residue based rations during the long-dry period of the subhumid zone in Nigeria. A total of 7 treatments of 4 goats each was utilised. All treatment groups had a basal diet of Digitaria smutsii hay and natural past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
5
17
1
Order By: Relevance
“…Furthermore, [21,22] in their study reported that, the milk yield of local Egyptian goats ranges between 0.66 and 0.80 L/d; while in Greece, the milk yield of local breeds of goats ranges between 0.55-0.75 L/d [23]. In Nigeria, the milk yield of Sokoto Red goats (local breed) was reported to give 0.62 L/d [24], 0.14 L/d [25], and 0.42 L/d [14], respectively. These findings are comparable to the milk yield reported for non-descript goats as observed in this present study but, lesser when compared to those of Nguni and Boer goats which indicates that, the milk production of Nguni and Boer goats are more in terms of quantity than other local goat breeds from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, [21,22] in their study reported that, the milk yield of local Egyptian goats ranges between 0.66 and 0.80 L/d; while in Greece, the milk yield of local breeds of goats ranges between 0.55-0.75 L/d [23]. In Nigeria, the milk yield of Sokoto Red goats (local breed) was reported to give 0.62 L/d [24], 0.14 L/d [25], and 0.42 L/d [14], respectively. These findings are comparable to the milk yield reported for non-descript goats as observed in this present study but, lesser when compared to those of Nguni and Boer goats which indicates that, the milk production of Nguni and Boer goats are more in terms of quantity than other local goat breeds from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that parameters such as litter size, birth weight and growth rate of offspring from birth to weaning are some indices of reproductive performance [7]. The reproductive function and capacity of goats in the tropics are affected by several factors such as nutrition [8], season [3,9], genotype [5,10] and diseases [10,11]. It has been shown that the low reproductive performance of these animals in north-eastern Nigeria is implicated to the traditional husbandry system, where no special care is given to the breeding stock and hence their performance remains perpetually low [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is a medium‐sized breed with reddish‐brown coat colour with a mature average live weight of 30 kg kept for its milk, meat and skin. Detailed descriptions of its milk composition (Malau‐Aduli and Anlade, 2002; Malau‐Aduli et al., 2003a), herd size (Gefu and Adu, 1982), production (Mathewman, 1980; Otchere et al., 1987), lactation (Ehoche and Buvanendran, 1983) and reproductive performance (Adu and Ngere, 1979; Malau‐Aduli et al., 2003b, 2004) have been documented. However, the production of these animals is limited by genetic and environmental factors such as nutrition, disease and their interactions that lead to poor reproductive performance.…”
Section: Introductionmentioning
confidence: 99%